Integration of Islamic Moral Values in Digital Literacy of Students in the 5.0 Era - Irhamullah; Jefri; Wahyu Hidayat; Resti Sulastri (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
The rapid development of technology in the era of 5.0 presents new challenges for the field of education, particularly in shaping learners’ character to be not only digitally competent but also grounded in Islamic moral values. In this context, the integration of Islamic ethical principles is crucial to ensure that digital literacy does not merely enhance technical abilities but also fosters ethical behavior in digital activities. This study aims to analyze how Islamic moral values can be effectively integrated into students’ digital literacy so that they are able to use technology wisely, responsibly, and in accordance with Islamic teachings. The research employs a qualitative approach with descriptive analysis through literature review and theoretical examination related to digital literacy, digital ethics, and Islamic moral values. The findings indicate that the integration of Islamic moral values can be implemented through the cultivation of digital ethics such as honesty, trustworthiness, responsibility, politeness in online communication, and critical thinking in evaluating information. Additionally, the use of digital learning media infused with Islamic values has been shown to increase students’ awareness of the importance of ethical behavior in digital spaces. In conclusion, digital literacy that aligns with Islamic moral values can serve as a strong foundation for learners in navigating the dynamics of technology in the era of 5.0, while also promoting the development of a generation that is both digitally proficient and spiritually moral